Revisiting the J-Curve of Indonesia-China bilateral trade - Salim, Agus; Pranolo, Andri; Hariyanti, Nunik; Fadillah, Dani; Khotimah, Husnul; Firdaus, Nalendra Putra (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
The examination of the J-curve effect has been grown primarily for the case of aggregate trade level in some countries. Most studies assume that the exchange rate affects the dynamics of aggregate trade balance symmetrically. To fill the gap of the empirical studies, this manuscript attempt to revisit the presence of J-curve and analyze the effect of Indonesian Rupiah vis-à-vis Chinese Yuan on bilateral trade balance between Indonesia and China, whether symmetric or asymmetric. We employ autoregressive distributed lag (ARDL) and its partial sum concept of nonlinear manner to estimate quarterly data from 2002:I to 2017:IV. The result shows evidence of the asymmetric effect of the exchange rate on the trade balance, and the nonlinear approach provides more support to discover the presence of the J-curve impact of bilateral trade between Indonesia and China.